The emotional labour of academic integrity: How does it feel? - Openo, Jason Aaron; Robinson, Rick (Canadian Perspectives on Academic Integrity, 2021)
Academic integrity is valued in all Canadian educational systems, yet no real accounting of academic integrity violations (AIVs) exists primarily because faculty under-report them. Numerous disincentives dissuade faculty from reporting AIVs, and voluntarily reporting violations increases emotional labour. Still, some faculty feel duty-bound to do so. This paper explores the neglected emotional experience when reporting AIVs using a phenomenological approach. Interviews with a purposive, homogenous sample of faculty at a small Canadian community college who reported AIVs reveal that reporting AIVs disturbed relationships with students, and that navigating bureaucratic processes, when other faculty choose not to, caused frustration. After reporting, faculty in this study felt alienated from the outcomes of their decisions. Still, they remained committed to reporting AIVs because it was part of their self-definition as educators to defend the innocent and protect the future. This small sample of faculty identify personal experiences and institutional barriers that may discourage faculty from reporting AIVs. Finally, the findings reveal a gap between faculty and international students’ understanding of academic integrity. Bridging this gap is important because of the intensified emotional and relational challenges arising from the more serious consequences of reporting AIVs involving international students. The findings reveal a need for faculty development opportunities that build intercultural competence and handle AIVs in a way that respects diverse worldviews and promotes the values of academic integrity.